Metreleptin Treatment in a Boy with Congenital Generalized Lipodystrophy due to Homozygous c.465_468delGACT (p.T156Rfs*8) Mutation in the BSCL2 Gene: Results From the First-year - Şervan Özalkak; Meliha Demiral; Edip Ünal; Funda Feryal Taş; Hüseyin Onay; Hüseyin Demirbilek; Mehmet Nuri Ozbek (Galenos Yayincilik, 2023)
Congenital generalized lipodystrophy (CGL) is a rare, autosomal recessive disorder characterized by an almost complete absence of body fat. In CGL, patients may have hyperphagia due to leptin deficiency. Recombinant human leptin (metreleptin) has been suggested as an effective treatment option. We present successful treatment with metreleptin in a boy with CGL and results from the first year of follow-up. An eight-month-old boy presented with excessive hair growth and a muscular appearance. On examination he had hypertrichosis, decreased subcutaneous adipose tissue over the whole body and hepatomegaly. Laboratory investigations revealed hypertriglyceridemia, hyperinsulinemia, elevated liver transaminases and low leptin levels. Molecular genetic analysis detected a homozygous, c.465_468delGACT (p.T156Rfs*8) mutation in the BSCL2 gene. A diagnosis of CGL type 2 was considered. Despite dietary intervention, exercise, and treatment with additional omega-3 and metformin, the hypertriglyceridemia, hyperinsulinemia, and elevated liver transaminase levels worsened. Metreleptin treatment was started and after one year hyperphagia had disappeared, and there was dramatic improvement in levels of insulin, hemoglobin A1c, triglycerides and liver transaminases. Hepatosteatosis was lessened and hepatosplenomegaly was much improved. Metreleptin appears to be an effective treatment option in children with CGL that remarkably improved metabolic complications in the presented case. Initiation of metreleptin treatment in the early period may decrease mortality and morbidity, and increase the quality of life in children with CGL.